Uang Komisi dalam Jual Beli Sepeda Motor dalam Perspektif Hukum Ekonomi Islam di Desa Sukamakmur Kecamatan Ajung Kabupaten Jember - Abdul Mun'im (ACTIVA: Jurnal Ekonomi Syariah, 2019)
This study aims to discuss the commission money on motorcycle buying and selling in the perspective of Islamic economic law. The purpose of this study is to describe how the form of commission money is given in buying and selling motorbikes in Sukamakmur Kec village. Ajung. Is Jember District in accordance with Islamic economic law or not. This research is qualitative research. How to collect data through three stages, namely interview, and observation. The data in this study consists of two parts, namely, primary and secondary data. The collected data was analyzed using qualitative descriptive methods using triangulation techniques. From the results of the study showed that the commission money in buying and selling motorbikes in Sukamakmur Village, Ajung District, Jember Regency was in accordance with Islamic law except for commissions with subsidized contracts.